Integration of nutrigenomics, melatonin, serotonin and inflammatory cytokines in the pathophysiology of pregnancy-specific urinary incontinence in women with gestational diabetes mellitus - França, Danielle Cristina Honorio [UNESP]; França, Eduardo Luzía; Sobrevia, Luis [UNESP]; Barbosa, Angélica Mércia Pascon [UNESP]; Honorio-França, Adenilda Cristina; Rudge, Marilza Vieira Cunha [UNESP] (Elsevier, 2023)
Gestational diabetes mellitus is an important public health problem and has been associated with the development of pregnancy-specific urinary incontinence. The interaction is related to hyperglycemia, and inflammatory and hormonal patterns, which favor functional alterations in different organs and systems. Several genes associated with human diseases have been identified and partially characterized. Most of these genes are known to cause monogenic diseases. However, about 3 % of diseases do not fit the monogenic theory due to the complex interactions between multiple genes and environmental factors, as in chronic metabolic diseases such as diabetes. The nutritional, immunological, and hormonal patterns associated with changes in maternal metabolism may influence and contribute to greater susceptibility to urinary tract disorders. However, early systematic reviews have not yielded consistent findings for these associations. This literature review summarizes important new findings from integrating nutrigenomics, hormones, and cytokines in women with Gestational diabetes mellitus and pregnancy-specific urinary incontinence. Changes in maternal metabolism due to hyperglycemia can generate an inflammatory environment with increased inflammatory cytokines. This environment modulated by inflammation can alter tryptophan uptake through food and thus influence the production of serotonin and melatonin. As these hormones seem to have protective effects against smooth muscle dysfunction and to restore the impaired contractility of the detrusor muscle, it is assumed that these changes may favor the onset of urinary incontinence specific to pregnancy.
Keywords: Epigenetic; Hormones; Hyperglycemia; Immunomodulation; Involuntary loss of urine